2009
DOI: 10.1016/j.bpj.2009.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Cell Durotaxis Depends on Substrate Stiffness Gradient Strength

Abstract: Mechanical compliance is emerging as an important environmental cue that can influence certain cell behaviors, such as morphology and motility. Recent in vitro studies have shown that cells preferentially migrate from less stiff to more stiff substrates; however, much of this phenomenon, termed durotaxis, remains ill-defined. To address this problem, we studied the morphology and motility of vascular smooth muscle cells on well-defined stiffness gradients. Baselines for cell spreading, polarization, and random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
319
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(368 citation statements)
references
References 47 publications
26
319
0
1
Order By: Relevance
“…As cells sense the stiff side, they exert larger forces which in turn could induce a polarization of the actin cytoskeleton toward the stiff side and thus promote durotaxis. Interestingly, qualitatively similar behavior has been observed for the durotaxis of vascular cells on defined stiffness gradients within a range of rigidities up to 80 kPa (47). The study observed a higher polarized behavior on gradient gels than on uniform substrates and a durotactic behavior enhanced by increasing the magnitude of gradients.…”
Section: Dynamics Of Focal Adhesions and Traction Force Measurements Onsupporting
confidence: 80%
“…As cells sense the stiff side, they exert larger forces which in turn could induce a polarization of the actin cytoskeleton toward the stiff side and thus promote durotaxis. Interestingly, qualitatively similar behavior has been observed for the durotaxis of vascular cells on defined stiffness gradients within a range of rigidities up to 80 kPa (47). The study observed a higher polarized behavior on gradient gels than on uniform substrates and a durotactic behavior enhanced by increasing the magnitude of gradients.…”
Section: Dynamics Of Focal Adhesions and Traction Force Measurements Onsupporting
confidence: 80%
“…It is known that substrate stiffness largely influences cell migration. Indeed, recent studies have shown that many different types of cells, including VSMCs, move towards stiffer substrates (Isenberg et al, 2009). Therefore, inter-EC junctions might provide the rigid scaffold required for efficient MC migration, because inter-EC junctions are supported by the actin cytoskeleton Phng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that the molecular composition of the pericellular environment regulates cell behaviors, but the mechanical properties also mediate cell responses. Cells sense and respond to differences in substrate rigidity, which has been shown to influence behaviors such as growth (2), morphology (3,4), migration (4,5), and differentiation (6 -8), although details of the mechanochemical mechanisms have not been fully elucidated.…”
Section: The Extracellular Matrix (Ecm)mentioning
confidence: 99%